Citrulline Is an Important Biochemical Indicator in Tolerance to Saline and Drought Stresses in Melon - Sebnem Kusvuran; H. Yildiz Dasgan; Kazim Abak (The Scientific World Journal)
Salt- and drought-induced alterations in citrulline were assessed in 4 local melon genotypes, 2 sensitive (CU-52, CU-94) and 2 tolerant (CU-196, CU-280), grown in vermiculite in a growth chamber. Salt and drought stresses were started using 30-day-old plants, with 250 mM NaCI and 45 mM PEG (−1.0 MPa) and continued for 12 days. After 12 days under salt and drought conditions, the citrulline contents were increased in the tolerant CU 196 to 25.10 μmol gDW−1 and 24.10 μmol gDW−1 for salt and drought stresses, respectively. However, the citrulline contents of the sensitive CU-52 were 11.68 μmol gDW−1 and 11.76 μmol gDW−1 for salt and drought, respectively. The striking alteration was obtained in the citrulline accumulation. The tolerant melons accumulated 2 times more citrulline than the sensitive melons. For assessing or screening melon genotypes in a large number of accessions or breeding lines for their tolerance to salinity and drought during their young plant stage, the amount of citrulline accumulation in response to the given treatments might be considered as a novel biochemical indicator of interest in early selection studies.